Inclusiveness of Gus Iqdam's Recitation in Embracing Inter-religious People - Muhammad Ilham Ahsanul Kholid (Islamic Thought Review, 2023)
This study aims to understand how Gus Iqdam promotes inclusiveness and tolerance between religious communities in his da'wah. It is also to discover what forms of inclusiveness and tolerance Gus Iqdam promotes. This article will also dig deeper into how Gus Iqdam embraces people of other religions in his da'wah and what factors affect inclusiveness and tolerance between religious communities in Gus Iqdam's recitation. This study uses qualitative research methods or qualitative research using observation-based qualitative research. This type of observation research allows researchers to systematically document and reflect on the activities and interactions of research subjects. The results showed that people from various religions and tribes were enthusiastic about Gus Iqdam's recitation, which was open without differentiating between faiths and tribes. Gus Iqdam is known as a preacher with an inclusive approach, which aims to create an inclusive and relaxed environment for all groups regardless of religion, tribe, or ethnicity. In Islam, inclusive da'wah refers to developing religious understanding and life that shows flexibility, tolerance, and respect for inclusiveness so that adherents of various religious sects or religions can coexist peacefully.